Analisis Dimensi Pembentuk Indeks Pembangunan Manusia (IPM) Provinsi Jambi 2010-2019 - Jasasila Jasasila (Ekonomis: Journal of Economics and Business, 2020)
Human development is a process and an outcome that is the process of enlarging people's choices but also becoming a goal. Human development implies that people must influence the processes that shape their lives. Human development is the development of society through the building of human capabilities, by society through active participation in the processes that shape life and society by improving their lives. It is broader than other approaches, such as the human resources approach, the basic needs approach and the human welfare approach. The problem of this research is how the development of the Human Development Index in Jambi Province in 2010-2019, the second problem is how to analyze the dimensions that form the Human Development Index in Jambi Province in 2010-2019, while the purpose of this study is, To determine the Development of the Human Development Index in the Province Jambi in 2010-2019 and to analyze the dimensions forming the human development index of Jambi Province in 2010-2019. The type of research that the writer uses in this thesis is the type of qualitative analysis and quantitative analysis. The data that is sought in this study is in the form of numerical data which includes data on life expectancy at birth, expectations of length of schooling and average length of schooling which are obtained from the official website of the BPS (Central Statistics Agency) Jambi Province. The results of this study indicate that during the period 2010 to 2019 the HDI of Jambi Province showed great progress. In 2019, the HDI of Jambi Province has reached 71 points, which means that it has increased from the “Medium” to “High” level compared to 2017. During the 2010-2019 period, the HDI of Jambi Province in the Health Sector has always shown an increase, the highest development was in 2019 of 0.23% and the lowest development was in 2017 at 0.07%. During 2010-2019 the HDI of Jambi Province in the Education Sector has always shown an increase, the highest increase in the indicator of long school expectancy (HLS) was in 2013 at 3.75 % and the lowest development was in 2019 at 0.23% and the highest development in the average length of school (RLS) indicator was in 2012 at 2.80% and the lowest development was in 2015 at 0.50%. During 2010-2019, the HDI of Jambi Province in the Decent Living Standard Sector has always shown an increase, the highest development was in 2018 at 4.82% and the lowest development was in 2013 at 0.80%.